2021
DOI: 10.3390/ph14121239
|View full text |Cite
|
Sign up to set email alerts
|

A Large Sample Retrospective Study on the Distinction of Voriconazole Concentration in Asian Patients from Different Clinical Departments

Abstract: Voriconazole (VRZ) is widely used to prevent and treat invasive fungal infections; however, there are a few studies examining the variability and influencing the factors of VRZ plasma concentrations across different clinical departments. This study aimed to evaluate distinction of VRZ concentrations in different clinical departments and provide a reference for its reasonable use. From 1 May 2014 to 31 December 2020, VRZ standard rates and factors affecting the VRZ trough concentration were analyzed, and a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Since the metabolism of voriconazole is regulated by liver enzymes ( Zhong et al, 2018 ), its overexposure may occur in patients with liver damage. Published studies demonstrated that reduced voriconazole elimination is significantly associated with impaired liver function, as indicated by elevated alanine transaminase ( Zhao et al, 2021b ), aspartate transaminase ( Li et al, 2017 ), direct bilirubin ( Zhao Y. C et al, 2021 ) and international normalized ratio levels ( Zhao et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the metabolism of voriconazole is regulated by liver enzymes ( Zhong et al, 2018 ), its overexposure may occur in patients with liver damage. Published studies demonstrated that reduced voriconazole elimination is significantly associated with impaired liver function, as indicated by elevated alanine transaminase ( Zhao et al, 2021b ), aspartate transaminase ( Li et al, 2017 ), direct bilirubin ( Zhao Y. C et al, 2021 ) and international normalized ratio levels ( Zhao et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, supratherapeutic trough concentrations of VRZ have been linked to adverse events. Compared with other populations (Zhao et al, 2021b;Chen et al, 2022), the initial exposure of VRZ in patients with liver dysfunction appears to be higher. With decreased liver function, the metabolism and excretion of drug are slowed down and VRZ can easily accumulate (Verbeeck, 2008;Gonzalez et al, 2014).…”
Section: Discussionmentioning
confidence: 62%
“…The TBIL level was associated with VCZ clearance in IFI patients with liver dysfunction ( Tang et al, 2021 ). TBIL level was also considered an independent factor influencing VCZ C 0 ( Cheng et al, 2020 ; Zeng et al, 2020 ; Zhao Y. et al, 2021 ). However, our results showed that levels of DBIL but not TBIL influenced VCZ C 0 and C 0 /C N .…”
Section: Discussionmentioning
confidence: 99%